The Effect of Produce Purchasing Behavior on Adult Obesity and Body Weight: Evidence from Household-Level Scanner Data. (August 2019) - Volpe, Richard; Cai, Xiaowei; Schroeter, Christiane; Mancino, Lisa
Abstract : We use household scanner data, paired with rich demographics and merged with self-reported measures of obesity and body mass index (BMI), to investigate the potential effects of fruit and vegetable purchasing behavior on adult obesity and body weight. We find that increasing household fruit and vegetable expenditure shares by one percentage point decreases the multiyear incidence of adult obesity by approximately 9 percent and average adult BMI by 1.4 percent, controlling for a host of potential confounding factors and measures of lifestyle choices. The results are robust to specification choice, although estimated impacts differ by gender. Our findings help quantify the potential impacts of government efforts aimed at increasing fruit and vegetable intake.